A RESEARCH ABOUT THE EFFECT OF ROLE STRESSORS ON BURNOUT - Kubilay ÖZYER (Fırat University, 2019)
Role stressors are situations that cause stress experienced people working within an organization. Roles stressors generally are accepted in the literature by two factors; role ambiguity and role conflict. Role ambiguity is caused by a lack of knowledge regarding work and role conflict arises from the fact that the person faces expectations that are incompatible with each other. On the other hand burnout are situations where working with people face to face emerging occupations and people often live in a state of exhaustion. If a person faces with role conflict or role ambiguity he or she can feel more burnout is the main problem of this study. To analyze this problem data was collected from 218 nurses via questionnaire. The data has analyzed and it has found that role ambiguity and also role conflict effect burnout syndrome. Furthermore, it has found role ambiguity and role conflict effect some sub dimensions of burnout. But these effect become different on sub dimensions of burnout.